Neutralitetsdoktrinens överlevnad under 1990-talets politiska påtryckningar - Elhachimi,Saad (2020)
With the foreign political turbulence after the fall of the Berlin Wall, the world came into a change. The post-cold war environment meant that the politics of the bipolarity no longer were the case. This period leads to pressure in redefining Sweden’s foreign and security policy, resulting in an emergence of a different commitment to the countries neutrality and non-alignment. In the light of Kjell Goldmann's Stability theory this study aimed to investigate the transformation of the neutrality doctrine. Three political changes indicated the strong links to foreign stability in Sweden’s neutrality policy. The analysis highlights how leadership used different political instruments for interpreting the declaration. Additionally, the study illuminates the political responsiveness between the parties, how the compliance in the Moderate party and the Social democrats, changed in the view of what the doctrines upheld functions could be. Their increased awareness, of the inevitable change, which would lead to a strive for higher international codependency.
Keywords: Neutrality; Non-alignment; Stability theory; Foreign stability; Policy change; Doctrine